Condition of coral cover in the waters of the Pieh Island Conservation Area, West Sumatra - Farma, Elmi Aulia; Thamrin, Thamrin; Effendi, Irwan (South East Asian Marine Sciences Journal, 2024)
Coral reefs are the main components of coastal and marine ecosystems and are important in maintaining coastal and marine functions. West Sumatra is one of the provinces in Indonesia whose territory faces the Indian Ocean and has a wide diversity of coral reef cover. This research aims to determine the condition of coral cover in the waters of the Pieh Island Conservation Area, West Sumatra. The method for collecting coral cover data uses UPT (Underwater Photo Transect) with a transect length of 50 meters and a frame size of 58 x 44 cm2, photographed every meter at 3 (three) station points. The research results show that the condition of coral cover on Pandan Island is 63.04% in the good category, Toran Island is 77.94% in the very good category, and Air Island is 88.30% in the very good category. The average coral cover condition at the research station was 76.42%. Based on KEPMEN LH No.4 of 2001 concerning Standard Criteria for Coral Reef Damage, it is included in the very good category